One-pot bioconversion of tomato waste into poly-gamma-glutamic acid (gamma-PGA) biopolymer by a novel biocatalyst - Nair, Pranav G.; Joseph, Emmanuel; Killi, Naresh; Konchada, Sravanya; Nisal, Anuya; Gundloori, Rathna Venkata Naga; Dharne, Mahesh S. (ACS Sustainable Chemistry & Engineering, 2021)
Landfilling of rotten tomatoes can lead to environmental instability and a huge economic loss to the producers. This letter reports an effective valorization of tomato waste into a promising biopolymer, i.e., poly-gamma-glutamic acid (gamma-PGA) by a novel biocatalyst Bacillus paralicheniformis NCIM 5769. The gamma-PGA is one of the most expensive biopolymers with multifarious applications in wound healing, drug delivery, and regenerative medicine fields. However, its adoption into various applications is finite due to its exorbitant production cost. Herein, rotten tomatoes (without additional nutrient supplementation) served as the chassis for the fermentative production of 40 g/L of highly pure gamma-PGA within 48 h at ambient temperature. Further, NMR, DSC, and TGA confirmed the purity of synthesized gamma-PGA identical to standard gamma-PGA. This process has potential in the commercialization of.-PGA by significantly reducing the production cost, followed by the effective utilization of tomato waste leading to United Nations Sustainable Development Goal 12 (i.e., ensure sustainable consumption and production patterns).
Keywords: Commercialization; Poly-gamma-glutamic acid; Rotten tomatoes; United Nations Sustainable Development Goals; Waste utilization

Effective valorization of blackstrap molasses to poly gamma glutamic acid (γ-PGA) using L-glutamic acid independent feeding approach and its significance as drought mitigator in wheat plant - Nair, Pranav G.; Dharne, Mahesh S. (Industrial Crops and Products, 2023)
One of the finest approaches towards sustainable waste management is its effective valorization to value-added products (VAPs). Waste valorization is garnering considerable attention since it delivers substantial advantages, including environmental stability and a sustainable and viable platform for producing different VAPs. One such VAP is the poly gamma glutamic acid (& gamma;- PGA), an extortionate biopolymer known to date. Its exorbitant cost is the main barrier preventing & gamma;- PGA from becoming commercially viable. Hence, the key to the successful commercialization of & gamma;- PGA is its sustainable and cost-effective production. In the present study, the ability of Bacillus paralicheniformis NCIM 5769 to utilize molasses for & gamma;-PGA production with minimal nutrients was investigated. Results showed that 30% molasses combined with 2% ammonium nitrate was the optimal medium for & gamma;-PGA production. Additionally, the anti-drought activity of the synthesized & gamma;-PGA was evaluated on wheat plants showing significantly higher shoot length, biomass content, and germination rate compared to the control group. These findings suggest that & gamma;-PGA produced from molasses has the potential to be used as a drought mitigator in wheat plant, thereby achieving the mission of circular economy and sustainable development goal (SGD) 12, i.e. pursuing sustainability patterns for consumption & production.
Keywords: Anti-drought; circular economy; Poly gamma glutamic acid; Sustainable; Waste valorization

Sustainable and cleaner production of poly-gamma-glutamic acid (γ-PGA) biopolymer using floral waste and its anti-staling properties - Nair, Pranav G.; Dharne, Mahesh S. (Journal of Cleaner Production, 2023)
The framework of sustainable development (SD) hinges on 17 different ideals established by the United Nations. This call for SD can be addressed by the circular bio-economy concept, which not only ensures effective waste management but also encourages its valorization and repurposing, hence fostering both ecological and economic stability. One-third of the world's floral production is in jeopardy, and because there are no potential solutions for sustaining floral waste, it inevitably ends up in landfills and riverine systems, which is detrimental to the environment. Therefore, in the present study, floral waste that was destined for landfills or water bodies was productively valorized to poly gamma glutamic acid (gamma-PGA), a high value biopolymer, with a yield of 40 g/L and productivity of 1.6 g/L/h employing an L-glutamic acid (L-GA) independent feeding approach. When gamma-PGA was coated onto Vitis vinifera grapes, it exhibited excellent moisture retention, reduced microbial contamination, and preserved the grapes' aesthetic characteristics and nutrient content. The weight loss study demonstrated that grapes coated with 1% and 2% gamma-PGA experienced significantly lower weight loss (13% and 14% respectively) compared to the control group (21.6%). Moreover, a 5-min dip coating time proved to be the most effective in reducing weight loss to 12.43%. Over a period of 14 days, the control group exhibited a remarkably high weight loss (41%) in contrast to the treated group, which showed significantly lower weight loss (16%). Our work is a fine example of how the circular bio-economy and waste valorization may be used to achieve the long-term objectives of sustainable development, economic stability, and food security.
Keywords: Bio-economy; Floral waste; L-GA independent; Poly-gamma-glutamic acid; Valorization